Analysis of Differences in Financial Performance Before and after the Implementation of the National Health Guarantee: (Case Study at Al Islam Hospital Bandung) - Iqbal, Mohammad; Affandi, Azhar; Hermawan, Atang (Pascasarjana Universitas Pasundan, 2023)
This research study aimed to analyze the financial performance of Al Islam Bandung Hospital before and after the implementation of the National Health Insurance (JKN) and identify the factors influencing its performance. The study focused on various financial ratios, including profitability, liquidity, and activity ratios. The findings revealed significant differences in several ratios, such as Return on Investment, Cash Ratio, Inventory Turnover, Receivable Turnover Period, and Total Asset Turnover, indicating a decrease in performance after the implementation of JKN. The factors affecting the financial performance of Al Islam Bandung Hospital were categorized into internal factors, competitor factors, BPJS Health factors, government policy factors, and pandemic factors. Internal factors, such as cash availability, logistics management efficiency, expense management, and asset growth, played a crucial role in sustaining the hospital's financial operations during the initial phase of JKN implementation. The increased involvement of competitor hospitals in the JKN program impacted patient visits to Al Islam Hospital, reducing its financial performance. BPJS Health factors, including tiered referral policies and payment delays, influenced the hospital's patient flow and financial stability. Government policies related to JKN implementation provided a wider scope of services but lacked regular tariff adjustments, leading to increased operational costs. Additionally, the COVID-19 pandemic further affected Al Islam Bandung Hospital's financial performance by reducing patient visits while increasing the need for additional resources to handle COVID-19 cases. In conclusion, the study highlights the changes in financial performance of Al Islam Bandung Hospital after the implementation of JKN and identifies factors such as patient numbers, payment periods, policy adjustments, and expense management as key contributors to these changes. Understanding these factors can help healthcare institutions adapt and improve their financial performance within the context of national health insurance schemes.